Pengaruh Kualitas Sumber Daya Manusia dan Tunjangan Kerja Terhadap Kinerja Pegawai Dinas Pendidikan, Pemuda dan olahraga Kabupaten Trenggalek - Hartatik, Sri (Universitas Islam Kadiri, 2024)
This research aims to: Analyzing the simultaneous significant influence of Human Resource quality and work benefit on employee performance ;examining impact Human Resource quality on employee performance ; assesing the influence of work benefits on employee performance This research uses Descriptive Quantitative. the population in this research is in the at the Department of Education, Youth and Sport in Trenggalek Regency.. The researcher does not specify a sample, because all members of the population will be examined. The technique is a method of data collection now. In this study, researchers used the software (software), Microsoft Office Excel 2007 to carry out a descriptive and statistical analysis software (software) Statistical Package for Social Sciences (SPSS) for Windows version 21.0 to carry out the test, test the classical, hypothesis testing and multiple linear regression analysis, , The research findings indicate a significant influence of Human Resource quality and job benefits on employee performance . meanwhile the most dominant influencingvariable is the Human Resource quality